The effects of Brazilian tea (Stachytarpheta jamaicensis) and Bitter kola (Garcinia kola) seed meal on the growth and gonad development of the African catfish Clarias gariepinus (Burchell, 1822) - Ekanem, Sunday Ben; Eyo, Victor Oscar; Okon, Esther Emmanuel (Ege Journal of Fisheries and Aquatic Sciences, 2017)
A 90-day study was undertaken to evaluate the effects of Stachytarpheta jamaicensis and Garcinia kola seed meal on the growth and gonad development of the African catfish, Clarias gariepinus. Ninety (90) fingerlings were stocked in nine rectangular concrete tanks (10 each) labeled Al, A2, A3, Bl, B2, B3, C1, C2 and C3 with a total water volume of 887.04 m3 .Three isonitrogenous diets (A, B, and C) with 40% crude protein including the control diet containing 0g of S. jamaicensis and 0g of G. kola meal, 70 of S. jamaicensis leaf meal and 35g of G. kola meal + 35g of S. jamaicensis leaf meal in the feed were fed to the fish at 5% body weight. Fish in A-series tanks were fed diet A, fish in B-series tanks were fed diet B while fish in C-series tanks were fed diet C. Weight gain, length gain, SGR, GR, and FCR were better in fish fed the diet A but not significantly different (P>0.05) from fish fed diet B and diet C. Female GSI, male and female gonad weight were better in fish fed diet A but not significantly different (P>0.05) from fish fed diet B and diet C. However, male GSI (1.39 ± 0.01) of fish fed the diet A was significantly different (P<0.05) from male fish fed diet B (0.94 ± 0.15) and diet C (0.95 ± 0.05). Fecundity of fish fed diet A (11,834 ± 1644eggs) was significantly different (P<0.05) from fish fed diet B (6375 ± 995eggs) and diet C (10,236 ± 896eggs). Histology of ovaries and testes of fish fed the three experimental diets showed normal distribution of oocytes and testicular cells. Our findings imply that the combination of G. kola seed meal and S. jamaicensis leaf meal in feed negatively affects the growth, fecundity, and gonad development of C. gariepinus which can be detrimental to aquaculture production.
Keywords: Stachytarpheta jamaicensis; Garcinia kola; growth; gonad development; fecundity; Clarias gariepinus